ABILITIES OF CELESTIAL OBSERVATIONS IN ASTRONOMICAL OBSERVATORY OF PHYSICS INSTITUTE IN OPOLE - Godlowski, W.; Szpanko, M. (Одеські астрономічні публікації, 2010)
We present possibilities of astronomical investigation in Astronomical Observatory in Opole. Our observatory uses two telescopes: Celestron CGE-1400 XLT (35 cm) and Meade LX200 (30 cm) with spectrograph and CCD Camera. Main topic of our observational investigation is connected with observations of variable stars, minor bodies of the solar system, blazers and the Sun.